The medieval construct of demonic evil: an inverted incarnation - Raftery, Margaret (University of the Free State, 2007)
This article explores the concept of inversion as an essential ingredient in the medieval understanding of Good and Evil. It argues that demonic evil is often, but here specifically in the Dutch rederijker drama Mariken van Nieumeghen, constructed and represented as an inversion of the incarnation of Christ. Christ is the true Logos, or Word, made flesh, offering love and reconciliation, teaching knowledge of the Father, and bringing salvation; the drama’s Moenen is the devil disguised in scholarly garb, offering Mariken wealth and pleasure as well as to teach her all languages and the seven liberal arts, b ut leading her ultimately to damnation. The inversion technique is structural in a further sense, as Mariken’s initiation into the world of evil is analysed as involving a series of inversions of the Catholic sacraments, all of which were either instituted by Christ or founded on the Church’s interpretation of events during his incarnation. Issues of power (including gendered power) attendant upon the dichotomy of inversion of the forces of Good and Evil in the play are also discussed.

Hierdie artikel ondersoek ’n aspek van die konsep van inversie as ’n onontbeerlike element van die middeleeuse begrip van die Goeie en die Bose. Die demoniese word dikwels as inversie en/of deur middel van inversie voorgestel, en hier word daar getoon hoe die demoniese identiteit in die rederykerspel Mariken van Nieumeghen spesifiek as ’n omkering van die Christelike inkarnasie gekonstrueer en voorgestel word. Terwyl Christus die ware Logos of vleesgeworde Woord is, wat liefde en versoening bied, kennis van die Vader leer en redding bring, is die drama se Moenen eintlik die duiwel (as geleerde vermom), wat vir Mariken rykdom en genot, asook kennis van alle tale en die sewe vrye k unste belowe, maar wat haar inderwaarheid slegs verdoemenis bied. Die inversietegniek struktureer die spel ook op ’n ander manier: daar word getoon hoe Mariken se inwyding in die wêreld van die bose hier geskied deur middel van ’n reeks omkerings van die sewe Katolieke sakramente (wat almal òf deur Christus self ingestel is, òf op die Kerk se interpretasie van gebeure tydens sy inkarnasie gefundeer is). Vraagstukke in verband met mag (insluitend dié van gender en mag) wat saamhang met die digotomie wat uit die inversie van die Goeie en die Bose in die drama ontstaan, word ook bespreek.
Keywords: Demonic evil; Inversion; Incarnation of Christ; Marieken van Nieumegen